RESEARCH OF HEAT EXCHANGE WING OF PROFILE NASA – 0021 - Manatbayev, R.K. (Recent Contributions to Physics, 2018)
In the report results of experimental research of heat exchange wing of profile NASA – 0021 with an environment presented.